2021
DOI: 10.1386/dbs_00020_1
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking luxury brands and sustainable fashion business models in a risk society

Abstract: This exploratory work investigates the burgeoning integration of ‘cradle to cradle’ practices into primary strategic activities of procurement, production and sales by ten London based fashion businesses, analysing how profits are derived from offsetting the high costs of sustainable inputs against savings from innovative strategic choices in the production value chain. This research was influenced by the background knowledge that in the global fashion industry, less than 1 per cent of the recycled textiles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Price is both a determinant and a barrier in forming more sustainable consumer behavior, according to the findings. Consumers who are more concerned about the environment are more willing to pay for this type of product [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Price is both a determinant and a barrier in forming more sustainable consumer behavior, according to the findings. Consumers who are more concerned about the environment are more willing to pay for this type of product [43].…”
Section: Methodsmentioning
confidence: 99%
“…The following is a discussion of each of the sustainability innovation practices in the textile industry as identified in the reviewed studies. Global Case study 3 firms [38] Brazil Survey 100 firms [39] The Netherlands Interview 12 individuals [40] India Survey 198 employees [31] NA Chemical composition [41] China Case study 48 firms [42] Germany Interview 64 experts [43] Italy Survey 696 consumers [44] Indonesia Survey 182 SMEs [45] UK Interview 10 firm owners [46] South Africa Interview 12 SMEs owners [47] Vietnam Interview 5 technical spec. and 1 supplier [11] Denmark Note: ECOD = ecodesign, LCAS = life cycle assessment, ECOL = ecolabel, MTRL = material, PCKG = packaging; CLNP = clean production, ECOE = ecoefficiency, WSTH = waste handling, SCMT = supply chain management, TECH = technology, ENZY = enzymatic textile processing; EMSY = environmental management system, COLB = collaboration, BMOD = business model, CLKN = culture and knowledge management, RISK = risk management.…”
Section: Themes and Subthemesmentioning
confidence: 99%
“…Environmental risks Natural disaster A natural disaster can be the excuse for various CSC risks counting shortage of material, process, and conveyance delays Grundmann et al ( 2013 ), Magnier et al ( 2019 ) Processing environment Some textile manufacturing processes are also impacted by their dispensation environment; this can negatively impact the job and occupied environment, affecting outputs and resource scarcities for other businesses Landi et al ( 2018 ), Wang et al ( 2022 ) Appliance maintenance Product excellence is also affected by poor recital and several industrial mishaps due to poor appliance maintenance Grundmann et al ( 2013 ), Kim and Wu ( 2021 ), Magnier et al ( 2019 ) 4. Tactical risks Business branding The initial step of occupational processes is Branding; it fosters customers whether to get manufactured goods or not; this can also upsurge the possibility of practising CSC in Textile sectors Dwivedi et al ( 2005 ), Olatubosun et al ( 2021 ) Apparent customers A CSC frequently fails due to a non-cooperative mode among clients and suppliers; there might be an absence of confidence and reliability in their goods Kazancoglu et al ( 2020a , 2020b ); Weber ( 2019 ) Balanced offers In the CSC, the allocation price of the resource is less than other process allocations. Providing additional bargains on their goods, not including a future operative analysis, monetary and business sufferers may appear Furferi ( 2021 ), Wang et al ( 2022 ) Vision statements An absence of effective corporate monitoring and future scrutiny significantly influences functioning, innovation, and market tactics for a sustainable CSC process Levanen et al ( 2021 ), Valentine et al ( 2017 ) Report governing ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deprived of past data, a productive supply chain is intolerable for apparent coming demand and costs Ambika and Srilekha ( 2021 ), Lahane and Kant ( 2021 ) 5. Quality risks Customer satisfaction Consumer happiness is the foundation of most successful businesses, yet customer gratification is predicated on the “value of money paid over a quality product.” When the eminence value falls, the risk price rises Chen and Lin ( 2021 ), Olatubosun et al ( 2021 ) Product feasibility Product recital normalises timeline making, product eminence, and productivity in the circularity; any fluctuations in performance are principal for financial and business risk Gigli et al ( 2019 ), Landi et al ( 2018 ), Lahane et al ( 2023 ) Product service life CSC also should emphasise excellent products. Low eminence products are expected to necessitate additional repair, reformation, and advancement: bad amenity generates life and eminence risks Ambika and Srilekha ( 2021 ), Lahane and Kant ( 2021 ), Wang et al ( 2022 ) Resale value From a commercial standpoint, reselling rates are well-thought-out based on product recital and quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors discovered a sustainable business model for Turkish firms in each sector and identified common characteristics between firms, such as having a strong relationship with stakeholders and receiving feedback from employees and suppliers. Another study [88] examined the effect of ESG issues on luxury fashion businesses by analyzing the policy documents of 10 fashion business owners, demonstrating a form of technology implementation aimed at achieving a circular business model. The analysis shows sustainability awareness and the implementation of a circular economy in the value system.…”
Section: Practicesmentioning
confidence: 99%